A Review of the Piston Effect in Subway Stations. (10th November 2013) - Pan, Song; Fan, Li; Liu, Jiaping; Xie, Jingchao; Sun, Yuying; Cui, Na; Zhang, Lili; Zheng, Binyang
Abstract : In recent years the piston effect in subways has become a topic of interest for researchers and engineers. Many publications have appeared on this topic, but reliable information is scattered and poorly organized. This review paper covers the latest publications on the piston effect in subways. We compile information about the mechanism of the piston effect, evaluate its influence, and describe how it can be effectively utilized.